Evaluation Of Operational Strategy In Area 4 PT Tirta Investama (AQUA) Pandaan - SEPTIAWAN, ROYNALDO DWI (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
PT Tirta Investama (AQUA) Pandaan is one of the companies that produce mineral water. The products produced are AQUA 1500 ml, 600 ml, 240 ml and Mizone. Although aqua became the first brand to produce Drinking Water in Packaging but the company still has to evaluate its strategy strictly because of many new competitors to improve operational efficiency at PT Tirta Investama. The production area in PT Tirta Investama (AQUA) Pandaan is divided into 4 areas. This study was conducted in Area 4 because the achievement of production targets was not always achieved at the maximum level based on Operational Efficiency indicators and Performance Efficiency Indicators. The type of this research is descriptive with observation data collection techniques, interviews and documentation.The results show that PT Tirta Investama (AQUA) operational performance of Pandaan 4 area is quite good, but the strategy management process still needs to be improved to achieve Operational Efficiency and Performance Efficiency of 90% from production machine capacity. Optimization of maintenance performance is required to support the operational performance of production in area 4. Therefore it needs careful planning, especially spare parts spare parts and adaptation of new parts so that the production process can run smoothly.Keywords: Operational Strategy, Strategy Implementation, Strategy Evaluation, Area 4 PT Tirta Investama (AQUA) Pandaan